The techniques The effect of a training program for the development of explosive power and the power that is characterized by speed on some skills (long pass, runningof describing in the journey of " Benefit and Consideration" by Abd EL latif al-Baghdadi - Dalfi, Takieddine; Hacene, Idir (Journal of Human Sciences, 2021)
The study aimed to find out the effect of a training program to develop explosive force and speed that characterizes speed on improving some skills the long pass and the running with ball and the shooting in football among school sports team pupils 12to 14 years of intermediate education in the state of Uum Al BouaghiWhere the researchers followed the experimental approach by applying a proposed training program and comparing the results of the pre and post tests for the experimental and controlling groups of the research sample and among the results that the study led to, that the proposed program has a positive effect on improving the skills of long pass and running with the ball and shooting in soccer among students..